The Influence of, Surface Roughness and Different Types of Coating and Implantation Materials on the Frictional Forces of Aesthetic NiTi Arch Wires - Maher Saad Mohammed; Sami AL-Juborri (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: The purpose of this in vitro study is that NiTi esthetic arch wires are preferred to match estheticbraces; but the presence of coating layer is greatly affect friction during sliding mechanics.The aims of this study were to evaluate the influence of surface roughness with the coating material types(coating and ion implanted) on the frictional force of coated nickel titanium wires.Methods: The sample of this study consisted of 140 segments of coated Nickle titanium arch wires for bothtests (friction test and roughness test) 70 segment for each test involving wire dimensions (0.016 × 0.022and 0.019 × 0.025 inches). The static frictional force was measured through pulling the wires through a setof ceramic brackets by the universal testing machine while, the surface topography of wires were assessedby using Atomic force microscope (AFM). The data were analyzed using one-way analysis of variance(ANOVA) and Tukey’s post hoc significance difference tests. Differences were considered significant atP<0.05.Results: The frictional forces of coated wires differ from uncoated control being higher in the control andpolymer coated wires and lesser in the rhodium, gold implanted and labial coated wires owing to differencesin the wire dimension, surface roughness, thickness of coating layer, and physical properties of coatingmaterials.Conclusion: when tested in vitro, rhodium implanted wires produce the least amount of friction, Surfaceroughness of fully coated arch wires was higher than non-coated counterpart and It appeared that frictionalforces does not correlated with the surface.